Simultaneous Treatment of Renal and Upper Ureteral Stone and Cysts With Percutaneous Nephrolithotomy and Cyst Laser Intrarenal Incision and Drainage - Hu, Xiaohui; Jiang, Kehua; Chen, Hongbo; Zhu, Shenliang; Zhao, Chunxiong (Urology Journal, 2018)
Purpose: To assess the feasibility and safety of percutaneous nephrolithotomy (PCNL) combined with cyst laser intrarenal incision and drainage in the management of renal and upper ureteral stones with ipsilateral renal cyst. Materials and Methods: Between March 2011 and March 2016, 28 patients with ipsilateral renal cyst in renal and upper ureteral stones underwent PCNL combined with cyst laser intrarenal incision and drainage. The perioperative evaluated variables included operation time, cyst size after surgery, complications and stone-free rate(SFR). Results: All patients successfully underwent the operation without conversion to open surgery. The mean operative time was 64.4±30.1 minutes; the mean hemoglobin reduction was 7.9±1.6 g/dL; the mean time to removal of nephrostomy tube and double J ureteral stent was 3.0±1.0 days, and 30.3±7.0 days; the mean hospital stay was 8.5±2.0 days. The SFR of all the patients was 89.3%(25/28), and no serious perioperative complications occurred. Conclusion: PCNL combined with cyst laser intrarenal incision and drainage is a feasible and safe approach for treatment of renal and upper ureteral stones with ipsilateral renal cyst.